2011
DOI: 10.1111/j.1447-0756.2010.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of exact delivery time in patients with preterm labor and intact membranes at admission by amniotic fluid interleukin‐8 level and preterm labor index

Abstract: Using markers reflecting inflammation in the uterus (amniotic IL-8 or vaginal fFN) and clinical symptoms (PLI), we may be able to predict the exact delivery time in preterm labor patients with intact membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…PTL was defined as those with regular uterine contractions and cervical changes effaced over 50%, and dilatation of the cervix or shortening of the cervical length (CL) <25 mm. The severity of PTL was evaluated using the preterm labor index (PLI), which we have previously reported as a clinical marker for PTL . When a patient with PTL was hospitalized, they were immediately treated by tocolysis by continuous intravenous infusion of ritodrine hydrochloride (maximum, 100 μg/min) to control uterine contractions.…”
Section: Methodsmentioning
confidence: 99%
“…PTL was defined as those with regular uterine contractions and cervical changes effaced over 50%, and dilatation of the cervix or shortening of the cervical length (CL) <25 mm. The severity of PTL was evaluated using the preterm labor index (PLI), which we have previously reported as a clinical marker for PTL . When a patient with PTL was hospitalized, they were immediately treated by tocolysis by continuous intravenous infusion of ritodrine hydrochloride (maximum, 100 μg/min) to control uterine contractions.…”
Section: Methodsmentioning
confidence: 99%
“…Preterm labor was defined by the presence of regular uterine contractions (6 hour or more), cervical changes of more than 50% effaced, and dilatation of the cervix or shortening of the cervical length to less than 25 mm before 37 completed weeks of gestation. The severity of PTL was evaluated by the PTL index (PLI), which we previously reported as a clinical marker for PTL …”
Section: Methodsmentioning
confidence: 99%
“…These inflammatory cytokines could activate decidual immune cells, and PGE 2 induces uterine contractions. High levels of serum and amniotic fluid inflammatory mediators were associated with APO, especially PTB . A systematic review reported a positive association between APO and inflammatory mediator levels in gingival crevicular fluid, which is an inflammatory exudate from the gingival margin or within the gingival crevice .…”
Section: Inflammatory Mediators Produced By Gingival Submucosamentioning
confidence: 99%